Capturing innovation in an in-house service deck - Isip, Ronald Fernandez; Talisayon, Serafin (Quezon City University of the Philippines Diliman, 2012)
There is high probability of innovation capture from the service desk as it serves as an interface with the end-users, but finding systematic methods for innovation for technologies supported are seldom available; and just following industry standards (such as with ITIL) may open to the dangers of core rigidity.
However, innovation is best captured at the fringes of an organization, where the service desk is actually located- through an innovation management framework. Outsourcing can be considered but may not be as effective for non-profit organizations and UN affiliated agencies who, besides from budgetary reasons also require institutional knowledge - hence, the in-house service desk is maintained, to manage end-user requests and to search and implement technology solutions.
This paper tries to address the needed balance and optimize in-house service desk capabilities through an innovation management framework (within the IOM ITCSC context)-a modification of the main processes of the ITIL framework merged within the innovation model by Tidd-Bessant (classifying innovations according to the Henderson-Clark typology). This is facilitated through a methodology that identifies the issues challenging the framework (on people, processes, products and partners); employs a communication strategy; designs and implements the framework; and devises evaluation methods for capturing ideas that leads to specific projects and activities resulting with a roadmap.
As innovation is a social practice, the innovation management framework is slated for continuous monitoring, study, and improvement, which will be benchmarked and hopefully can be made applicable to other similar support units within IOM, other agencies, and other industries that are into IT Service Management (ITSM).
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Information resources management; Management; In-house service desk